Cohort Intelligence for Solving Travelling Salesman Problems - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2017)
As demonstrated previously, the performance of the Cohort Intelligence Algorithm (CI) algorithm was quite satisfactory for solving combinatorial problem such as Knapsack Problem (KP) (Int J Mach Learn Cybern, 2014 [1]).